Development of a home-based practical skills program for preschoolers with developmental delays - Esmalde, Billy S. (2009)
This study developed a home-based practical skills Program for children with developmental delays. The program was based on the eating, dressing, and toileting needs of children and the teaching skills of their parents. The research sample consisted of ten parents of children with developmental delays who were ages five to ten years old. Survey questionnaires were initially given to qualified parents and their responses became the bases for the practical skills program. Results showed that there was a significant difference in the practical teaching skills of parents after the program. Parents were willing to teach their children and became effective educators given the right materials.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Life skills -- Philippines -- Quezon City; Developmentally disabled children -- Education (Preschool) -- Philippines -- Quezon City; Home schooling -- Philippines -- Quezon City; Education, Preschool -- Parent participation -- Philippines -- Quezon City; Children with disabilities -- Education (Preschool) -- Philippines -- Quezon City